Study of the power of a mobile radio transmitting equipment - Pasarelski, Rosen (Yearbook Telecommunications, 2017)
The article presents basic methods for the research of the power of mobile radio transmitting equipment. Block configurations have been prepared to measure parameters such as maximum output power, off-mode power for time division duplex, and power factor in a neighboring channel of a mobile radio transmitting stations. The main objectives of the research are: â€¢ to establish that, under normal external conditions of measurement, the maximum output power is within the range of the power demanded by the manufacturer. â€¢ to check the radio station’s ability to keep the transmitted power in off state below a preset value. â€¢ to determine whether the measured relationship is within the limits set by the European Technical Specifications. As a contribution of the author to each study are presented specific stipulations, norms and procedures for taking measurements.